The death or injuries suffered by public health workers: An examination of the Philippine government’s response amid the COVID-19 pandemic - Perez, Joseph Raphael Lazaro (Animo Repository, 2021)
The researchers explored the liability of the Philippine National Government vis-a-vis the injuries and death suffered by public health workers during the COVID-19 pandemic. The researchers sought to address the adequacy of the legal framework surrounding the pandemic response of the country and if the response prior and during the pandemic contributed to the damages sustained by public health workers. The research focuses on the actions done by the Executive and Legislative branch. The laws passed by Congress concerning the preparation for national health emergencies and the allocation of the budget, specifically for the Department of Health were discussed and analyzed. Moreover, the researchers also reviewed the pandemic response of the Philippine government and compared it with neighboring countries in Southeast Asia to determine whether there was negligence on the part of the Philippine government. The researchers used the doctrine and requisites of state liability in assessing the liability of the Philippine government to its public health workers. To conclude the study, the researchers found that the measures taken by the Philippine government satisfied the requisites of state liability and therefore recommended the amendments to be done on the Magna Carta of Public Health Workers.